Bioimpedance Analysis–Guided Volume Expansion for the Prevention of Contrast-Induced Acute Kidney Injury (the BELIEVE Pilot Randomized Controlled Trial) - Sarassawan Kananuraks (2020)
© 2020 International Society of Nephrology Introduction: Peri-procedural i.v. fluid administration is important for the prevention of contrast-induced acute kidney injury (CI-AKI). However, standardized fluid management protocols may not be suitable for all patients. We therefore wished to determine whether an individualized fluid administration protocol guided by measuring extracellular water (ECW) using bioimpedance analysis (BIA) would be safe and would reduce the incidence CI-AKI compared to a standardized fluid administration prescription. Methods: In this pilot, randomized, parallel-group, single-blind, controlled trial, we compared the effect of BIA-guided isotonic bicarbonate administration according to the ratio of ECW to total body water (ECW/TBW) to our standard isotonic bicarbonate protocol in regard to the safety and efficacy of preventing CI-AKI in chronic kidney disease patients undergoing elective cardiac angiography. Our primary outcome was the incidence of CI-AKI, which was defined as a ≥0.3 mg/dl or 150% increase in serum creatinine concentration within 48 to 72 hours after cardiac angiography. Results: We studied 61 patients, 30 in the bioimpedance group and 31 in the control group. Age was similar (72.5 ± 7 vs. 71.4 ± 7.9 years), as were body mass index (25.5 vs. 25.8 kg/m2) and baseline serum creatinine (1.3 ± 0.3 vs. 1.4 ± 0.4 mg/dl). The peri-procedural fluid volume administered was significantly greater in the BIA-guided hydration group (899.0 ± 252.7 ml vs. 594.4 ± 125.9 ml, P <.01). The incidence of CI-AKI was 3.3% in BIA-guided hydration group and 6.5% in the control group (relative risk = 0.52, 95% confidence interval = 0.05−5.40, P = 1.00). Adverse events reported were comparable between groups (6.7% vs. 6.5%, P = 1.00). Conclusions: The overall incidence of CI-AKI after cardiac angiography in our patients with mild-to-moderate renal insufficiency was lower than anticipated. Isotonic bicarbonate administration guided by bioimpedance measurements was safe, and probably led to a lower incidence of CI-AKI, although this not reach statistical significance.